Optimization of green open space in Ambon City - Selanno, F.M.; Sitanala, M.R.; Santoso, P.; Arinah, H. (2022)
The increase in population in Ambon City has resulted in increased space requirements and impacts the conversion of green areas into built-up areas. This indirectly impacts the decline in environmental quality, marked by an increase in the concentration of greenhouse gas (GHG) emissions in the air. The Green Open Space (GOS) arrangement program involves efforts to reduce GHG emissions in Ambon City. However, in reality, the allocation of space to develop green open space in Ambon City still does not meet the 30 standard or is still lacking 737.8 ha. This study aims to obtain information about the arrangement of green open spaces in Ambon City. The interview method was conducted in a structured manner with a questionnaire. SWOT analysis was used to analyze internal factors and external factors. The results showed that the critical strategies in optimizing Ambon City's green open space were to improve the quality of green open space by planting plants that have high GHG emissions absorption potentials, such as Samanea saman, Pterocarpus indicus, and Acacia mangium. Conduct harmonization and socialization with other institutions such as the Ambon City Satpol PP and green open space users to increase the supervision of green open space. Using the basic green coefficient as the primary condition for obtaining a Building Permit (IMB). The present study recommended that future research on green open spaces in Ambon City should focus on other influencing elements including geography, climate, socio-culture, and so on. © Published under licence by IOP Publishing Ltd.